PERANCANGAN PLTS ON GRID SEBAGAI SISTEM CATU DAYA KAWASAN JATILUWIH - Dimas, Dimas; I Nyoman Satya Kumara, I Nyoman Satya Kumara; Sukerayasa, I Wayan (Program Studi Teknik Elektro UNUD, 2023)
Jatiluwih is a tourist village that was declared by UNESCO as one of the locations of world cultural heritage in 2012. Being recognized as a World Heritage Site, the Jatiluwih Area is not allowed to undergo any development that could damage the area's image. To support Jatiluwih as a green and sustainable area, this study proposes the installation of Grid-Connected Solar Photovoltaic Systems (PLTS) on rooftops to serve as the power supply system for the area. The objective of this study is to assess the rooftop solar power plant's capability and its energy production to meet the energy needs in the Jatiluwih WBD Area.Based on the survey, there are 45 buildings to support tourism activities in the Jatiluwih WBD Area, with a total daily energy requirement of 225.37 kWh. According to the established criteria, five buildings meet the requirements for installing rooftop PLTS. In the design of the rooftop PLTS, two scenarios are used: the load requirement scenario and the roof area scenario. The research results indicate that the installed rooftop PLTS capacity based on the load requirement for the Dukuh Baturan Villa, Warung Dhea, and Bhuana Agung Restaurant buildings is 2.05 kWp, for the Restoran Iga Lawar building is 2.46 kWp, and for the Teras Subak Homestay building is 1.2 kWp. Based on the roof area, the Dukuh Baturan Villa building has a capacity of 9.8 kWp, Teras Subak Homestay has 23.4 kWp, Warung Dhea has 10.6 kWp, Restoran Iga Lawar has 16 kWp, and Bhuana Agung Restaurant has 6.5 kWp.The rooftop PLTS system on these five buildings in Jatiluwih, using the roof area scenario, can generate an energy output of 270.35 kWh/day, thereby fulfilling the energy requirements of the 45 buildings.